Impact of maternal HBsAg carrier status on pregnancy outcomes in Duhok city, Iraq - Amira S. Khalil; Nawfal R. Hussein; Maida Y. Shamdeen (Asian Pacific Journal of Tropical Biomedicine, 2017)
Objective: To investigate the relationship between hepatitis B virus (HBV) positivity and pregnancy outcomes. Also, the association between HBV-related risk factors and HBV status was studied. Methods: A total of 100 HBV positive pregnant women were recruited and the pregnancy outcomes were compared with 301 HBV negative women. Blood samples were collected and tested for HBV by HBsAg ELISA. Data were collected for recruited subjects using interview questionnaire. Results: Data analysis showed that 51/100 (51%) of the HBV-positive subjects gave a history of HBV in the family which was significantly higher than that of HBV-negative patients [41/301 (13.6%) P = 0.001]. A significant association was found between positive history of surgery and HBsAg positivity (P = 0.009). Then, pregnancy outcomes were stratified according to the HBV positivity. No significant association was found between HBV status and pregnancy outcomes (P > 0.05 for all). Conclusions: Positive family history of HBV and previous surgical procedures are associated with higher rate of HBV positivity. No association is found between HBV positivity and pregnancy outcomes.